Governance of low carbon energy system transitions a case study from North Rhine Westphalia, Germany. - Philipp,Schepelmann
This brief shows how investments in climate mitigation can be implemented and how these are embedded in multilevel governance based on the experience of Germanys North-Rhine Westphalia in implementing low-carbon system transitions.